Perkembangan Strategi Pengobatan β-Thalassemia - Komang Ria Yuliana Santhi; Putu Ristyaning Ayu Sangging; Anisa Nuraisa Jausal; Helmi Ismunandar (CV. Jasa Sukses Abadi, 2025)
β-thalassemia is an inherited blood disorder caused by mutations in the β-globin gene that reduce or eliminate β-globin chain synthesis, leading to hypochromic microcytic anemia and significant morbidity worldwide. The disorder is prevalent in South Asia, Southeast Asia, the Mediterranean, the Middle East, India, and Africa, with approximately 1.5% of the global population identified as carriers. Severe complications, including iron overload, skeletal deformities, heart failure, and multi-organ damage, contribute to its substantial global health burden. This narrative literature review synthesizes evidence from PubMed, Cochrane, and Google Scholar to examine conventional and emerging therapeutic strategies for β-thalassemia, with particular emphasis on recent advances in gene therapy. Standard management relies on regular blood transfusions and iron chelation, which remain supportive and are associated with long-term complications. Hematopoietic stem cell transplantation is the only established curative treatment, especially effective in pediatric patients with matched HLA donors, although its availability is limited. Novel pharmacologic agents, such as luspatercept and mitapivat, have demonstrated reductions in transfusion requirements and improvements in hemoglobin production. Additional approaches, including fetal hemoglobin induction and modulation of iron metabolism, show encouraging potential. A major breakthrough is CRISPR-based gene therapy using exagamglogene autotemcel (Casgevy), approved by the FDA and EMA in 2024, with phase 3 trials reporting transfusion independence in more than 90% of patients and significant quality-of-life improvements. Despite persistent challenges related to cost, access, and long-term safety, these advances indicate a paradigm shift toward precision medicine with curative potential for β-thalassemia.